2007
DOI: 10.1093/annonc/mdl498
|View full text |Cite
|
Sign up to set email alerts
|

Estimates of the cancer incidence and mortality in Europe in 2006

Abstract: The total number of new cases of cancer in Europe appears to have increased by 300,000 since 2004. With an estimated 3.2 million new cases (53% occurring in men, 47% in women) and 1.7 million deaths (56% in men, 44% in women) each year, cancer remains an important public health problem in Europe and the ageing of the European population will cause these numbers to continue to increase even if age-specific rates remain constant. Evidence-based public health measures exist to reduce the mortality of breast and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
1,286
4
101

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 2,457 publications
(1,400 citation statements)
references
References 15 publications
9
1,286
4
101
Order By: Relevance
“…Our cancer patients and controls differed significantly due to age because breast cancer is a disease mainly prevalent in older women [24], whereas fibroadenoma is the most common benign breast tumor in adolescent girls and young women [38]. In spite of age difference found between the groups compared we did not adjust Cd concentration in breast tissue for age assuming that being a possible environmental-estrogen and accumulating in a human body it could simultaneously explain significance of age to the disease, especially knowing that breast cancer is a disease of postmenopausal women.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Our cancer patients and controls differed significantly due to age because breast cancer is a disease mainly prevalent in older women [24], whereas fibroadenoma is the most common benign breast tumor in adolescent girls and young women [38]. In spite of age difference found between the groups compared we did not adjust Cd concentration in breast tissue for age assuming that being a possible environmental-estrogen and accumulating in a human body it could simultaneously explain significance of age to the disease, especially knowing that breast cancer is a disease of postmenopausal women.…”
Section: Resultsmentioning
confidence: 96%
“…There was no a significant difference according to Cd found in urine and breast tumor tissue of both smoking differentially cancer patients and controls (p>0.05). [24]. About half of breast cancer cases can be explained by known risk factors related to the reproductive life, inheritance and socioeconomic status [25,26].…”
Section: Resultsmentioning
confidence: 99%
“…1,2 The widespread use of serum prostate specific antigen (PSA) testing along with increasing public awareness of prostate cancer has resulted in a significant increase in the proportion of patients with clinically localized tumors at the time of diagnosis who likely will not die of the disease. 3 Localized prostate cancers exhibit high levels of genetic, biological and clinical heterogeneity, 4,5 and current prognostic tools (based upon clinicopathologic parameters) are imperfect predictors of disease course.…”
mentioning
confidence: 99%
“…Some authors estimated that HPV-related cancers at penile, anal, and oropharynx sites are rare among men, occurring in about 1-6/100,000 in the general population [39]. It is estimated that penile cancer amounts to 1/100,000 inhabitants in the Western world, while increases in the Latin America area (1.5-3.7/ 100,000) and East Africa (2.8/100,000) [29,55]. HPV DNA is found in approximately 40-50 % of all penile cancers of the penis and epidemiological studies confirmed the predominant role of HPV 16 and 18 [5].…”
Section: Related Pathologiesmentioning
confidence: 99%